PENGETAHUAN DAN SIKAP IBU TERHADAP INISIASI MENYUSUI DINI (IMD) DI PMB LISMARINI PALEMBANG - Junay Darmawati; Maritje Rombe; Zulaikha Agustinawati; Afwan Syarif (Avicenna: Jurnal Ilmiah, 2023)
Background: Early Initiation of Breastfeeding is the process of breastfeeding babies immediately after birth, where babies are allowed to find their own mother's nipple (not thrust into the nipple). The purpose of this study was to obtain an overview of the knowledge, attitudes of mothers and the role of midwives towards early breastfeeding initiation (IMD) at BPM Lismarini Palembang. Method: This study used a descriptive survey method with a "Quantitative approach. The population taken was all postpartum mothers at BPM Lismarini Palembang totaling 46 respondents. The research sample used "Saturated Sampling", which is taking all the existing population. Results: Univariate data analysis obtained respondents who did IMD as many as 33 (71.7%), and who did not do IMD as many as 13 (28.3%). While the knowledge of respondents was found to be good knowledge as many as 25 (54.3%), those with less knowledge were 21 (45.7%), and the attitude of respondents was found to be positive as many as 35 (76.1%), who were negative as many as 11 (76.1%). Conclusion: postpartum women in Lismarini midwife Palembang have initiated breastfeeding with good knowledge and attitude.